Science–practitioner partnerships for sustainable development - Hope, R.; Charles, K. J.; Grafton, R. Q.; Olago, D.; Salehin, M.; Hossain, M. A.; Peters, R.; Gren, A.; Woldehanna, T.; Ibrahim, M.; Chowdhury, E. H.; Alam, M. M.; et al. (Nature Portfolio, 2024)
Science funding could contribute more towards achieving the United Nations Sustainable Development Goals. Science– practitioner partnerships illustrate how a patient and outcome-based approach could improve water security for millions of vulnerable people.